PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING SEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII IPA 1 - Kristianto, Nova; Marini, Marini (Epsilon: Jurnal Pendidikan Matematika, 2020)
Abstract: Learning outcomes are something that students achieve or obtain after following the learning process based on certain criteria in measuring the achievement of the learning objectives themselves. Based on the data of students studying grade XII IPA 1 SMA Negeri 4 Metro in the odd midterm assessment of the 2018/2019 school year obtained an average score of 67 students with only 38.5% of students who were able to exceed KKM. With the number of students consisting of 26 students only 10 students who get grades above KKM. This is still lower than the expected minimum completion criteria of 75. The low learning outcomes are influenced by many factors including the use of improper learning models. One of the models that can improve students' learning outcomes is the Discovery Learning model. The purpose of this study is to improve students' math learning outcomes by using the Discovery Learning model. The percentage of students who scored â‰¥ 75 in cycles I, II and III was 50%, 69%, and 81% with grade average scores of 70, 72, and 77. This data shows that learning outcomes have been achieved based on the achievement indicator set, which is 75% of students get a score of â‰¥ 75. So the results of this study show that the learning model of Discovery Learning can improve the results of mathematics learning students of grade XII IPA 1 SMA Negeri 4 Metro.